Chocolate in health and nutrition - Preedy, Victor R.; Watson, Ronald R. [ (Ronald Ross)] (Nitrition and health, 2013)
Annotation : Chocolate in Health and Nutrition represents the first comprehensive compilation of the newest data on the actions of the flavonoids and microorganisms associated with the beneficial effects of chocolate. This unique text provides practical, data-driven resources based upon the totality of the evidence to help the reader understand the basics, treatments and preventive strategies that are involved in the understanding of the role chocolate may play in healthy individuals as well as those with cardiovascular disease, diabetes or neurocognitive declines. Of equal importance, critical issues that involve patient concerns, such as dental caries and food preferences in children, potential effects on weight gain, addiction and withdrawal are included in well-referenced, informative chapters. The latest research on the role of chocolate in normal health areas including mood, pain and weight management, cardiovascular disease and related conditions are presented. Chocolate in Health and Nutrition provides health professionals in many areas of research and practice with the most up-to-date, well referenced and comprehensive volume on the current state of the science and medical uses of chocolate